NECESIDAD DE REFORMAR EL CÓDIGO DE LA NIÑEZ Y LA ADOLESCENCIA, EN LO QUE TIENE QUE VER CON LAS PENSIONES ALIMENTICIAS SUPLIDAS POR LOS ABUELOS COMO OBLIGADOS SUBSIDIARIOS - Guerrero Idrovo, Eduardo José (2016)
This paper whose theme is "NEED TO REFORM THE CODE OF CHILDREN AND ADOLESCENTS WHAT YOU HAVE TO DO WITH ALIMONY SUPPLIED BY GRANDPARENTS AS REQUIRED SUBSIDIARY" is framed to solve social and legal problems, since today generates social alarm, from a humanitarian point of view, in regard to maintenance payments by those jointly responsible, among these, uncles, brothers, grandparents, who are forced to comply with a responsibility stipulated by law, without taking into account that these people also have their children and families who remain, perhaps having just enough to cover their expenses, with jobs that allow them to live in a limited way as being low income, how is may they impose a burden, not to mention in the case of senior age they have to fulfill this obligation, including cases are evidenced in which to not cover the payment of pensions will go to prison, so much is being violated rights that are established in our Constitution which states that no imprisonment for debt, to live a decent life, the right to inviolability of life, physical, mental, moral integrity, and where all these rights of solidarity, more in an effort to solve this problem responsible go has increased abuse to third parties, who have to solve this problem, to meet an alien responsibility over this leads to the directly responsible and more justified increase its irresponsibility, as in the case of elderly people who meet this obligation, cross circumstances too uncomfortable because of their age are limited to income and even get pensions with which they have reached a limited basis for their medicines, but 6 despite all this, the protagonists of these laws briefly and without seeing the future consequences, made reforms that instead of solving the various problems aggravate. It is unfair to demonstrate the current situation being experienced by this group of people, who in some cases by not complying with payment of maintenance go to prison, being affected more than the economic part, the psychological part, because look deprived of their liberty entails entering a state of depression, because to the extent that even impact on their health, since logically the money, perhaps making an effort or borrowing will succeed, but having lived recover those moments that even criminals are arrested as these innocent people in every sense of the word go to prison to fulfill a responsibility that is not theirs; while directly responsible not aware of what is happening and still fulfill what belongs to him; all this creates not only economic but psychological problem in jointly liable, and where is what is stipulated in our Constitution. With regard to this problem, which draws much attention, it seeks to provide solutions to protect the child and force the obligor ie holders of the right to food (mother - father) who must meet their responsibility, without harming others